Free Writing Technique in Teaching Writing Skill in EFL Classroom - Isni, Paizatul (VELES Voices of English Language Education Society, 2018)
The purpose of this research was to find out the effectiveness of free writing technique in teaching writing for the tenth graders of SMA NW Wanasaba in the school year 2016-2017. Designed as pre-experimental research by using one group pre-test and post-test, it examined a sample of the tenth grade which consisted of 20 students. Writing test was the instrument used to collect the data. In collecting the data, pre-test and pos-test were given to the sample. The data were analyzed through parametric statistic by using SPSS 17.0 for windows. Since the mean score of the pre-test was lower than the mean score of the post-test; it meant that this technique was effective. After submitting the data to a paired samples t-test, it was found that there was a significant difference in the mean scores between the pre-test and the post-test, t(df=19)=-28.803 at p=0.000; it meant that the null hypothesis was rejected and alternative hypothesis was accepted. Thus, this technique was significantly effective in teaching writing for the tenth graders of SMA NW Wanasaba in the school year 2016-2017. Considering the process and the results of this research, the present researcher suggested that the English teacher use free writing technique in teaching writing.